Post-infectious pseudoaneurysm after coronary angioplasty using drug-eluting stents (Indian Journal of Case Reports, 2021)
Pseudoaneurysms may represent a risk for serious unfavorable outcomes. Pseudoaneurysm of the coronary arteries is also associated with about 80% of coronary stent infections. We present the case of pseudoaneurysm of the left circumflex coronary artery, due to infection with Staphylococcus aureus after drug-eluting stents implantation. Coronary stent infection can present as a mycotic aneurysm or pseudoaneurysm as in this case.